2014
DOI: 10.1155/2014/674094
|View full text |Cite
|
Sign up to set email alerts
|

Low-Grade Malignant Triton Tumor of the Neck: A Case Report and Review of the Literature

Abstract: Rhabdomyoblastic differentiation in a malignant peripheral nerve sheath tumor (MPNST) is termed malignant triton tumor (MTT), a rare neoplasm that poses a diagnostic dilemma in the differential diagnosis of neck masses and portends poor prognosis. We report a sporadic case of MTT of the neck in a 23-year-old female. We present the pathological findings. Immunohistochemistry confirmed the neurogenic origin with S-100 expression and the rhabdomyoblastic differentiation with desmin and vimentin positivity. Radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Sporadic MPNSTs are rare, occurring in only 0.001% of the general population [3]. MTT is also associated with NF-1 in 69% of cases [16], and, otherwise, arises secondary to radiation therapy [17] or is sporadic [18]. The present patient had a sporadic MTT, since there was no history of NF-1 or radiation therapy.…”
Section: Discussionmentioning
confidence: 66%
“…Sporadic MPNSTs are rare, occurring in only 0.001% of the general population [3]. MTT is also associated with NF-1 in 69% of cases [16], and, otherwise, arises secondary to radiation therapy [17] or is sporadic [18]. The present patient had a sporadic MTT, since there was no history of NF-1 or radiation therapy.…”
Section: Discussionmentioning
confidence: 66%
“…MPNSTs with elements of rhabdomyoblastic differentiation are termed as malignant triton tumors (MTTs). MTTs are referred to as a mosaic tumor due to their muscular and neurogenic components [ 12 ]. Masson was the first to report the presence of rhabdomyoblasts in this neurogenic tumor and described them as rhabdomyomas of the nerve [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nerve sheath differentiation is confirmed by S-100 protein and Leu-7 (CD57) positivity. Rhabdomyoblastic differentiation is confirmed by immunohistochemical positivity for desmin, actin, and myogenin [ 3 , 12 ]. Through these findings, the diagnosis of MTT can be positively made and the proper course of treatment can be pursued.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, these cells (like the tumor cells of RMS) are positive for desmin and myogenin/MyoD1. Malignant Triton tumors are regarded to behave in an aggressive fashion, even more than usual MPNST, [22,23,30,31] though head and neck cases described as ''low-grade'' have been reported [32,33]. It has been suggested that tumors in the sinonasal tract have a more indolent course than those arising in other head and neck sites (however, at least some of those indolent ''malignant Triton tumors'' could in fact represent the newlydescribed ''low-grade sinonasal sarcoma with neural and myogenic features,'' a tumor that lacks myogenin/MyoD1 expression) [34,35].…”
Section: Malignant Triton Tumormentioning
confidence: 99%